The value of extended good quality transurethral resection of bladder tumour in the treatment of the newly diagnosed bladder cancer - Mohamed Adel Atta (Taylor & Francis Group, 2017)
Objective: To report our experience for the initial management of patients with newly diagnosed bladder tumours using our team approach for each case and using an aggressive extended transurethral resection of bladder tumour (TURBT) in order to investigate the real need for a routine ‘second-look’ cystoscopy in the current era. Patients and methods: The study included 50 consecutive patients admitted to the urology department, of our tertiary care centre, for management of newly diagnosed bladder cancer. Exclusion criteria included past history of bladder tumour, palpable mass on bimanual examination under anaesthesia, presence of residual tumour at the end of resection, and patients with tumours of the bladder dome as thorough resection is difficult to achieve in this area without an attendant risk. Patients that had pathologically confirmed carcinoma in situ were also excluded. White-light cystoscopy was used in all of the cases. Extended TURBT was defined as resection of the whole tumour, resection of the tumour base and 1 cm of apparently normal bladder wall around the circumference of the tumour. Results: The median (range) age of the patients was 52 (39–60) years. After initial TURBT, 10 patients (20%) were identified as having muscle-invasive bladder cancer. Of the remaining 40 patients, three had low-grade Ta disease, and so second biopsies were not taken. The remaining 37 patients had T1, grade 2–3 disease and none of them had evident residual disease at the site of tumour resection. Conclusion: Re-staging TURBT could be safely omitted for select groups of patients. An experienced surgeon and teamwork, together with an extended TURBT can accurately achieve complete tumour resection, with accurate tumour staging, on initial resection.